Improvement of structural characteristics and in vitro digestion properties of zein by controlling postharvest ripening process of corn. (December 2022) - Zhao, Chengbin; Li, Qi; Hu, Nannan; Yin, Huanhuan; Wang, Tianchi; Dai, Xianglin; Zheng, Mingzhu; Liu, Jingsheng
Abstract: The newly harvested corn was stored at constant temperature (15 and 25 °C) and relative humidity (55%). The structural characteristics and in vitro digestion properties of zein as well as their structure-function relationship during postharvest ripening of corn were analyzed. The free sulfhydryl content and surface hydrophobicity decreased and the disulfide bonds and absolute value of ζ-potential increased during postharvest ripening of corn for 56 days at two storage temperatures. The particle size and polydispersity index reached the minimum values when postharvest ripening for 28 days. The association of hydrogen bonds for zein was decreased and more β-sheets were transformed into random coils in the postharvest ripening period, leading to the reduction in thermal stability and enthalpy change of zein. In addition, the molecular weight of α-zein decreased when postharvest ripening at 15 °C for 28 days, and changed little during postharvest ripening at 25 °C. In vitro simulated digestion experiment proved that the maximum degree of hydrolysis of zein was appeared when postharvest ripening for 28 days at both two storage temperatures, which was higher at 15 °C than at 25 °C. This indicated that appropriate postharvest ripening behavior could improve the digestibility of zein. The reduction of protein aggregation extent and thermal stability as well as enhanced disordered secondary structure of zein might be important factors to improve its digestibility during the postharvest ripening. The results suggested that controlling the postharvest ripening process of corn could modify the structure of zein and improve its digestion properties. Graphical abstract: Image 1 Highlights: Postharvest ripening of corn was performed at constant temperature and humidity. Aggregation, thermal stability and ordered secondary structure of zein reduced. Degree of hydrolysis for zein was highest by postharvest ripening for 28 days. Improvement of zein digestibility was related to its structural modification. Controlling postharvest ripening process of corn improved digestion property of zein.